A Tracer Study on Child Participation in Child Councillor Programmes Aimed towards Development of the Child Friendly Cities Initiative - Amelia Alias; Nurfaradilla Mohamad Nasri; Mohd Mahzan Awang (MDPI AG, 2023)
The Child Friendly Cities Initiative introduced by UNICEF aims to help local governments realise child rights by utilising the UN Convention on the Rights of the Child as its foundation. Using Lundy's model of child participation, which focuses on spaces, voice, audience, and influence, this study assesses young people's participation as child councillors in two programmes in one city in Malaysia. Ten young people who were former child councillors in one state in Malaysia participated in this study. This study employed thematic analysis in analysing the data obtained using focus groups. Based on the data presented, it was clear that adult (the responsible party) understanding of meaningful child participation is still weak. This study offers substantial contributions to the limited body of literature on child participation in Malaysia by focusing on the difficulties of former child councillors in engaging in meaningful participation. Thus, more efforts (for example, by using participatory methods) are needed to educate the responsible party on the importance of addressing the power dynamic between children and adults so that children can participate effectively in decision-making processes.